Synod on the Freedom of Conscience A Thorough Examination during the Gathering Held in the Year 1582 in the City of Freetown - Coornhert, D.V (Bibliotheca Dissidentium Neerlandicorum, 2008)
This is the first English translation of a pivotal work in the history of religious tolerance. In Synod on the Freedom of Conscience (1582) the Dutch humanist Dirck Volckertszoon Coornhert (1522-1590) provides one of the first book-length pleas for religious freedom published in the West. His central concern in his writings and exchanges with ministers of the Reformed Church was the safeguarding of freedom of conscience, the chief cause, he believed, for which the struggle against Habsburg Spain was being waged. The imaginary Synod, held in "Freetown," gathers together chief Catholic and Protestant leaders and theologians who engage in spirited debates on such matters as religious diversity, the freedom to criticize, the norms used to determine what constitutes heresy, freedom of the press, and the role of the state in the suppression of heresy. Each session concludes with remarks by the irenic Gamaliel (Coornhert's alter ego), who shows that both parties sin equally on the side of intolerance and pleads for the tolerant alternative. In this work Coornhert continues an Erasmian theme which would be picked up again in the following century by the Remonstrants and Hugo Grotius.